Teste de caminhada de seis minutos vs shuttle walk teste endurance: responsividade ao broncodilatador em pacientes com bronquiectasia - Boldorini, Jacqueline Cristina (2015)
Introduction: As a consequence of the structural changes in the pulmonary parenchyma, the main impact of bronchiectasis (BCT) is the worsening in lung function, characterized by the obstructive spirometric pattern and, in a subgroup of patients, restrictive. In obstructive patients, it is common the use of bronchodilator (BD). Aims: To investigate which field test, six-minute walk test (6MWT) or endurance shuttle walk test (ESWT), is more responsive to detect functional improvement after BD, to compare the physiological responses between 6MWT and incremental SWTI and to verify the differences in the physiological responses in the 6MWT and ESWT among patients presenting with obstructive and restrictive ventilatory disorders (OVD and DVR, respectively). Methods: This is a randomized, double blind, placebo (PL) controlled crossover study, in which 32 patients with BCT performed, on separate days (48 hours), the ISWT, 6MWT and ESWT, preceded by either PL or BD (400 µg of salbutamol). The cardiopulmonary and metabolic parameters were monitored during all tests by a telemetry system of the expired gases. Results: There was no statistically significant difference in distance walked between the ESWT-BD and 6MWT in the PL and BD conditions (910 ± 589 m, 526 ± 80 m, 527 ± 86 m). The distance walked and the time duration time of the test in the 6MWT and ISWT were statistically different (527 ± 86 m and 6 ± 0 min vs. 443 ± 119m and 7 ± 1 min, respectively). Patients with OVD and RVD presented with similar physiological responses at the peak of exercise. Conclusion: ESWT is the most suitable test to assess the acute effects of BD on functional response; the 6MWT and ISWT elicit similar physiological responses at peak exercise and the type of ventilatory disorder cannot be differentiated by the performance on the ESWT and 6MWT.